Strategy for Improving Clean Water Distribution Services by Village-Owned Enterprises (Bumdes) in Sumbertlaseh Village - Sumiati, Sumiati; Hariyani , Septiana; Surjono, Surjono (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
This study aimed to develop strategies to improve clean water distribution services in Bumdes Sumbertlaseh Village because the distribution of clean water in the village is not optimized. The analysis used the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to formulate a strategy for enhancing clean water distribution services in the village. Within the SWOT analysis framework, the satisfaction level is represented by values ranging from 1 to 4, with 1 indicating low satisfaction and 4 indicating high satisfaction. The SWOT analysis concluded that clean water distribution services were in quadrant V. The appropriate strategy in this situation was market penetration and product development. In market penetration, Bumdes Sumbertlaseh Village could implement strategies such as providing additional services or enhancing the quality of existing services to retain and attract new customers. Meanwhile, in product development, Bumdes Sumbertlaseh Village could implement strategies such as constructing new pipeline networks, expanding existing networks to cover unreached areas, or improving the reliability and efficiency of existing distribution systems.